Tunable hyperbolic apodizer - Ojeda Castaneda, Jorge; Ledesma, Luis; Valencia, Ricardo (Photonics Letters of Poland, 2015)
We unveil the use of two grey level masks for controlling continuously the attenuation of a spatial filter, which has an exponentially decreasing hyperbolic profile. We present analytical expressions that help to visualize the influence of our proposed grey level masks for reducing the side-lobes of a 1-D point spread function. Full Text: PDF References P. Jacquinot and B. Roizen-Dossier, "Apodisation," in Prog. Opt. 3, E. Wolf editor (North Holland, 1964) pp. 29-186. DirectLink C. W. McCutchen, "Generalized Aperture and the Three-Dimensional Diffraction Image", J. Opt. Soc. Am. 54, 240 (1964). CrossRef H. Arsenault and A. Boivin, "An Axial Form of the Sampling Theorem and its Application to Optical Diffraction", J. Appl. Phys. 38, 3988 (1967). CrossRef C. W. McCutchen, "Convolution relation within the three-dimensional diffraction image", J. Opt. Soc. Am. A 8, (1991). CrossRef J. E. A. Landgrave and L. R. Berriel-Valdos, "Sampling expansions for three-dimensional light amplitude distribution in the vicinity of an axial image point", J. Opt. Soc. Am. A 14, 2962 (1997). CrossRef A.W. Lohmann, J. Ojeda-Casta-eda and P. Rodríguez-Montero, "Axial irradiance shaping with binary polar curves", Opt. Comm. 108, 42 (1994). CrossRef J. Ojeda-Castafieda, L. R. Berriel-Valdos, and E. Montes, "Bessel annular apodizers: imaging characteristics", Appl. Opt. 26, 2770 (1987). CrossRef J. Ojeda-Casta-eda, and A. Díaz, "High focal depth by quasibifocus", Appl. Opt. 27, 4163 (1988). CrossRef J. Ojeda-Casta-eda and L. R. Berriel-Valdos, "Arbitrarily high focal depth with finite apertures", Opt. Lett. 13, 183 (1988). CrossRef J. Ojeda-Casta-eda and L. R. Berriel-Valdos, "Zone plate for arbitrarily high focal depth", Appl. Opt. 29, 994 (1990). CrossRef J. Ojeda-Casta-eda, E. Yépez-Vidal and E. García-Almanza, "Optical processor arrays for controlling focal length or for tuning the depth of field", Phot. Lett. of Poland 2, 162 (2010). DirectLink Jorge Ojeda-Castaneda, Emmanuel Yépez-Vidal, Eloy García-Almanza, and Cristina M. Gómez-Sarabia, "Tunable axial bursts using annularly distributed phase masks", Phot. Lett. of Poland 4, 115 (2012). DirectLink Jorge Ojeda-Castaneda, Sergio Ledesma and Cristina M. Gómez-Sarabia, "Hyper Gaussian windows with fractional wavefronts", Phot. Lett. of Poland 5, 23 (2013). CrossRef W. W. Bell, Special functions for scientists and engineers (Van Nostrand, London, 1968)